Validation protocol for the evaluation of space-borne lidar particulate back-scattering coefficient bbp - Vadakke-Chanat, Sayoob; Jamet, Cédric (Frontiers in Remote Sensing, 2023)
Space-borne lidar measurements from sensors such as CALIOP were recently used to retrieve the particulate back-scattering coefficient, bbp, in the upper ocean layers at a global scale and those observations have a strong potential for the future of ocean color with depth-resolved observations thereby complementing the conventional ocean color remote sensed observations as well as overcoming for some of its limitations. It is critical to evaluate and validate the space-borne lidar measurements for ocean applications as CALIOP was not originally designed for ocean applications. Few validation exercises of CALIOP were published and each exercise designed its own validation protocol. We propose here an objective validation protocol that could be applied to any current and future space-borne lidars for ocean applications. We, first, evaluated published validation protocols for CALIOP bbp product. Two published validation schemes were evaluated in our study, by using in-situ measurements from the BGC-Argo floats. These studies were either limited to day-or nighttime, or by the years used or by the geographical extent. We extended the match-up exercise to day-and nighttime observations and for the period 2010-2017 globally. We studied the impact of the time and distance differences between the in-situ measurements and the CALIOP footprint through a sensitivities study. Twenty combinations of distance (from 9-km to 50-km) and time (from 9 hours to 16 days) differences were tested.A statistical score was used to objectively selecting the best optimal time-distance windows, leading to the best compromise in term of number of match-ups and low errors in the CALIOP product. We propose to use either a 24h/9km or 24h/15km window for the evaluation of space-borne lidar oceanic products. This was required for converting the bbp(700) from the BGC-Argo data set to bbp(532) for comparison with the CALIOP-estimated bbp(532). Similarly, the annual MODIS Aqua derived SST values were also obtained from the NASA website. The Kd values from MODIS Aqua with 8-day average and 9 km resolution were also downloaded to be used in the depth averaging of BGC-Argo bbp as in Lacour et al., 2020.